PROGRES FUNDRAISING ZAKAT PADA BAITUL MAL ACEH PERIODE 2016-2020 - Shafwan Bendadeh (SYARIAH: Journal of Islamic Law, 2021)
Fundraising zakat is the main responsibility of amil. In fulfilling this responsibility, Baitul Mal Aceh (BMA) has succeeded in doing so. Therefore, this study aims to determine the growth of zakat collection in BMA in the 2016-2020 period in terms of nominal, sources, and efforts made in collecting zakat. To achieve this goal, this research uses a case study. The findings show that the amount of zakat collected during this period increased significantly to a total of more than Rp. 248.44 billion, although it tends to fluctuate. The increase was above the national average. In terms of sources of zakat, professional zakat income is more dominant. To support the success of zakat collection efforts, BMA and the provincial government continue to strive to obtain new sources of zakat income, form a Zakat Collecting Unit (UPZ) and conduct massive socialization of zakat to the community.